From a Book on Architecture to a Book of Pleasure: Ca’fer Efendi’s Risāle-i Mi'māriyye, 1614 - Gül Kale (Hart, 2023)
In conjunction with Mimar Sinan’s autobiographical memoirs, Ca’fer Efendi’s Risāle-i Mi'māriyye (Book on Architecture), penned around 1614, represents a unique primary source, not only within the Ottoman Empire but also in the broader Islamic world. Despite being one of the few texts authored by a scholar exploring the intricate interplay between architecture, diverse knowledge modalities, and artistic practices, the manifold implications and underlying aspirations of the Risāle, in terms of its connection to book cultures and writing traditions, remain inadequately comprehended. This article endeavors to shed light on specific sections from the Risāle, aiming to elucidate the ethical, social, and intellectual incentives that impelled a scholar like Ca’fer Efendi to undertake the writing of a book on architecture and the life of the chief architect, Mehmed Agha. To commence, we shall delve into the Risāle’s intended audience, considering the perspective of both its author, a member of the erudite class, and his patron, Mehmed Agha. Subsequently, we will probe how Ca’fer Efendi endeavored to underscore the architect’s and architecture’s social and ethical significance within his work, catering to his scholarly readership. This article will further explore the perception of architecture as a conduit for wisdom and knowledge, a rationale that elevated its standing within the hierarchy of sciences and ultimately facilitated a scholar’s authorship of a dedicated architectural book. Finally, we will delve into how an architectural publication transcended the realm of mere readerly pleasure, evolving into an integral component of Ottoman gift culture, thereby fostering the notion of architecture as a gift to society.